Compliance with intangible assets disclosure requirements: study of Portuguese non-financial companies - Azevedo, G.; Oliveira, J.; Couto, M. A. F. (Contaduría y Administración, 2019)
The present study aims to identify the degree of compliance with the intangible assets disclosure requirements outlined in the Accounting and Financial Reporting Standard (Norma Contabilística de Relato Financeiro – NCRF) 6 - Intangible Assets. It also seeks to analyse the factors influencing compliance with intangible assets mandatory disclosure requirements. An analysis of the 500 largest companies ranked by Exame Magazine, 2010, which are subject to the general Portuguese Accounting Standards System (Sistema de Normalização Contabilística - SNC), was conducted to check whether their Financial Statements for the years 2010 (transition year) and 2011 were made available on their websites. The methodology chosen to answer the research questions and achieve the proposed objectives was the content analysis of the financial statements of a sample of 37 Portuguese unlisted companies. The data collected in 2010 and 2011 allowed the construction of an index of intangible assets and the identification of disclosure explanatory factors. We tested six hypotheses for a possible association between the disclosure index and six explanatory variables through analysis, descriptive statistics, normality, differences in means, correlation and regression. Our results show an average of 30% in the disclosure index for intangible assets. Contrary to what was expected, results confirm that the adoption of SNC did not cause a higher level of disclosure over time. Companies’ size is the most influencing factor, indicating that larger companies disclose information on intangible assets basically to reduce agency costs, political costs related to their public visibility, and in such a way manage the relationship with their relevant stakeholders.